Shared Governance and It's Role in Higher Education - Robert E. Cipriano Dr. (Academic Chairpersons Conference Proceedings, 2022)
For approximately the past seventy-five years, shared governance has been the overriding principle that guides decision-making in American Colleges and universities. The core notion of shared governance is that both faculty and administrators have important roles to play in setting university policy. Recently, has shared governance merely become a catchphrase that has radically different meanings to different people? This interactive workshop will provide attendees with the tools to fully understand the roles and responsibilities that both faculty and administrators must play to foster a shared governance on their campus.
Keywords: Governance; Decision Making; Morale of Faculty and Administrators